The effect of nicotine patches on craving in the brain: A functional MRI study on heavy smokers. Issue 39 (September 2018) - Liberman, Keliane; Van Schuerbeek, Peter; Herremans, Sarah; Meysman, Marc; De Mey, Johan; Buls, Nico
Abstract: Background: Smoking is a common phenomenon and kills over 6 million people every year. Many smokers try to quit smoking by using nicotine replacement therapy (NRT). Most of the time, relapse occurs in less than six months after finishing the program of NRT. We performed a single blinded study in which our aim was to figure out what the effect of the nicotine patch is on craving in the brain of smokers deprived from smoking. Methods: Five heavy smokers (Fagerström Test for Nicotine Dependence ≥4) underwent a functional magnetic resonance imaging (fMRI) in 4 random conditions: smoking (S); smoking deprivation (SD); SD combined with a NP (SD + NP); SD combined with a placebo patch (SD + PP). Visual stimulation provoked craving in block design by randomly displaying images of smoking related scenes. After image preprocessing, a fixed-effect analysis was performed to compare average group activations. The Questionnaire for Smoking Urges (QSU) was obtained before and after each scan. Results: The fMRI results showed higher activation in areas involved in craving in S compared with SD + NP, SD + PP, and SD. In the SD + NP, limbic circuit and attention area were higher activated compared with SD and SD + PP. The SD + PP and SD showed higher activation in the frontal cortex and limbic system compared with S and SD + NP. Nonsmokers showed higher limbic activation compared with SD. The QSU increased significantly after the fMRI experiment in S ( P  = .036). The SD had higher QSU scores compared with the S before ( P  = .002), and also after ( P  = .022) the fMRI experiment. The NP showed lower scores than the SD before the experiment ( P  = .046). Conclusion: The fMRI experiment revealed lower activity in areas associated with attention when subjects were nicotine deprived (SD + PP and SD). Areas involved with craving showed less activity when nicotine is present (S and SD + NP). The QSU showed a significant difference between SD and when nicotine is present (S and SD + NP).